Product Design of Electronic Pocketbooks (MAMABOOKS) for Oral Health Care for Pregnant Women - Ferdiana Maharani; Syamsulhuda Budi Musthofa; Farid Agushybana (GLOBAL HEALTH SCIENCE GROUP, 2024)
According to Riskesdas data, the highest proportion of dental problems in Indonesia is dental caries which reached 45.3%, and as many as 45.7% were experienced by women, which is higher than the male group which only amounted to 44.8%. In the female group, oral care is much more important during pregnancy, breastfeeding, and menopause. According to research, the reason pregnant women do not maintain their oral health is because they do not know that during pregnancy they are more prone to oral diseases, especially gingivitis. Based on this, there is a need for health promotion in pregnant women. This study aims to conduct research and development of educational media in the form of material in electronic pocketbooks that will make it easier for mothers to access various information related to oral health maintenance in pregnant women. The method used is a qualitative method with several pregnant woman at Candilama Healthcare. The results showed that maximum education needs to be improved in pregnant women at Candilama Health Center, Semarang City, Central Java, there is a need for flexible educational media such as Mamabook electronic pocketbooks to increase literacy and education on oral health maintenance in pregnant women, the process of making mamabooks through the stages of needs analysis (need assessment), The process of making a mamabook goes through the stages of product design, expert validation, product trials, then product results containing oral health maintenance during pregnancy (dental and oral diseases of pregnant women, food diets, proper brushing of teeth), as well as quizzes on the knowledge and attitudes of pregnant women towards oral health. From the results of interviews and observations, it was found that there were no differences in characteristics between the intervention group and the control group.